Nation branding of Colombia among international stakeholders - Doria Villa, Alfonso Jose; San José Iglesias, Rafael; Martínez Pantoja, Yadira Ixchel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis explores the nation branding of Colombia from two different perspectives: the narrative constructed by Colombia’s brand managers and the perceptions and attitudes of the international stakeholders, specifically potential visitors and investors. The thesis uses a mixed-methods approach, including in-depth interviews with key figures involved in Colombia’s nation branding efforts and a survey targeting international respondents. The analysis reveals how Colombia’s nation brand campaigns have aimed to reshape the country’s image from one associated with conflict and drug trafficking to one that celebrates cultural richness, biodiversity, hospitality, and innovation. The results suggest that while nation brand managers’ efforts have been increasingly strategic and visually cohesive, international perceptions still include some negative associations. However, the thesis also finds growing recognition of Colombia’s touristic appeal, creative industries, and environmental assets. The thesis recommends stronger alignment between policy and branding messages, the use of internationally recognized cultural figures in campaigns, and greater coordination between government agencies to enhance Colombia’s global image.
Vedoucí práce: Rafael San José Iglesias
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses